BOOSTING LEARNING INDEPENDENCE: THE ROLE OF YOUTUBE, CREATIVITY, AND PEER INFLUENCE IN VOCATIONAL EDUCATION - Karuni, Radita Dayang; Fauzi, Achmad; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
In the era of an independent curriculum, students not only follow directions but are actively involved in learning which has a positive impact in facing changes and challenges in the future. This research aims to test the effect of YouTube social media, creativity, and peers on learning independence. This research design uses quantitative descriptive causal research methods. The population in this study were students department of Office Management and Business Services, Public Vocational High Schools 48 Jakarta. The sampling technique uses probability sampling techniques Stratified Sampling. The data used is primary data in the form of questionnaires distributed to respondents. The data analysis method is using SmartPLS 4.0. The results of this study indicate: (1) there is a positive and significant influence between YouTube social media on learning independence, (2) there is a positive and significant influence between creativity on learning independence, (3) there is a positive and significant influence between peer on learning independence. It means that if YouTube social media, creativity, and peers are used well in learning, it can increase student learning independence.